Stretch‐Induced Invasion: Stretch Induces Invasive Phenotypes in Breast Cells Due to Activation of Aerobic‐Glycolysis‐Related Pathways (Adv. Biosys. 7/2019). Issue 7 (12th July 2019) - Ansaryan, Saeid; Khayamian, Mohammad Ali; Saghafi, Mohammad; Shalileh, Shahriar; Nikshoar, Mohammad Saied; Abbasvandi, Fereshteh; Mahmoudi, Morteza; Bahrami, Farideh; Abdolahad, Mohammad
Abstract : In article number1800294, Mohammad Abdolahad and co‐workers report the role of cell stretching (as a model of biomechanical variations) in cell migration and invasion capacity using human normal and cancerous breast cells. Several analyses indicate that the cell‐stretching process could increase the migration and invasion capabilities of normal and cancerous cells, respectively.